An International Framework for Eco-Industrial Parks, Version 2.0 - United Nations Industrial Development Organization (World Bank, Washington, DC, 2021)
The aim of this publication is to provide an international framework (the "framework") which defines the basic requirements and performance criteria needed for an industrial park to qualify as an Eco-Industrial Park (EIP). It summarizes the areas in which the international organizations that have authored this framework — the United Nations Industrial Development Organisation (UNIDO), the World Bank Group, and the Deutsche Gesellschaft für Internationale Zusammenarbeit (GIZ) GmbH — have aligned to define an Eco-Industrial Park (EIP). The purpose of this publication is three-fold, namely: (i) to assist stakeholders to develop and transition to EIPs; (ii) to consistently engage with, encourage, and recognize EIPs; and (iii) to improve the performance, sustainability and inclusiveness of the industrial sector and move toward an international standard on EIPs. UNIDO, the World Bank Group, and GIZ are supporting governments and industrial park practitioners to develop EIPs in different countries and contexts. EIPs can be defined as industrial areas that promote cross-industry and community collaboration for common benefits related to economic, social and environmental performance. These goals are incorporated into the siting, planning, management, and operations of EIPs.Industrial parks are known by different names, including: industrial areas, industrial zones, industrial investment regions, special economic zones, and industrial corridors, and they are planned and developed for industrial activities and associated commercial and infrastructure services. The concentration of economic activities in industrial parks require that they are sustainable. There are currently a number of tools and processes which assist governments and industrial park stakeholders to implement inclusive and sustainable industrial development. However, a consolidated and targeted framework for EIPs is largely lacking at the international level. Increasingly, countries and industrial park stakeholders request ‘standards’ or benchmarks for pursuing sustainability as envisioned by EIPs. An innovative approach to such requests is to set "prerequisites" or "sustainability performance requirements" 1 for industrial parks, covering regulatory compliance and socio-economic, environmental, and management standards. These standards provide benchmarks for assessing existing industrial parks, retrofitting existing parks, or planning new EIPs. The EIP Framework presented in this document contains these prerequisites and performance requirements, which are outlined in tables in Section 4. These are international and inclusive in scope, and are relevant to all industrial parks, irrespective of what they are called. They are also relevant to stakeholders in the private and public sectors in which these industrial parks are located. The EIP Framework can inform stakeholder networks, and be used by UNIDO, the World Bank Group and GIZ to promote EIPs globally. Legislation by national governments of the regulations, activities and structures governing industrial parks varies considerably across the world, and so the framework recognizes the need to consider local contexts and sensitivities when applying these requirements.